Histopathological Changes in the Chorionic Villi and Endometrial Decidual Tissues in the Product of Conception of Spontaneous Abortion Cases - Makaju, R.; Shrestha, S.; Sharma, S.; Dhakal, R.; Bhandari, S.; Shrestha, A.; Tamrakar, S. (Kathmandu University Medical Journal, 2017)
Background Spontaneous abortion refers to a pregnancy that ends spontaneously before the fetus has reached a viable gestational age or expulsion or extraction of an embryo or fetus weighing 500 g or less from its mother. The Maternal Mortality Morbidity Survey of Nepal 2008/09 reported that 7% of maternal deaths in Nepal were due to complications related to abortion. Objective The main objective of this study was to examine the histopathological changes in the chorionic villi and endometrial decidual tissue in products of conception obtained from women with spontaneous abortion. Method This is a retrospective study of 111 patients admitted in the Department of Obstetrics and Gynecology at Dhulikhel Hospital, Kathmandu University Hospital (DH-KUH) with the diagnosis of spontaneous abortion during the period of January 2013 to January 2014. Result Among 111 cases of spontaneous abortions, products of conception was seen in 73 (65.77%) and with only one cases of choriocarcinoma. Majority of cases belongs to age group 21-30 years. The most common decidual changes were inflammation (41.4%) followed by fibrin deposition 29.7%. Majority of the cases shows hydropic changes as histopathological changes in chorionic villi. In the present study, minimum age of lady was 15 years and the maximum age was 45 years and the mean age was 25.09±5.58 years at the time of abortion. Among the cases, maximum 69 (62.2%) of them belonged to age group 21-30 years. Correlating the age group with number of abortions was found to be significantly different (Chi-square= 92.35, df= 3, p < 0.001) among four different age groups. Conclusion The histopathological diagnosis of spontaneous abortion will help in further management of the patient. Further study is required to know the cause of different histopathlogical changes in villi as well as in the decidua.